A Case Report of Sequential Use of a Yeast-CEA Therapeutic Cancer Vaccine and Anti-PD-L1 Inhibitor in Metastatic Medullary Thyroid Cancer - Del Rivero, Jaydira; Donahue, Renee N.; Marté, Jennifer L.; Gramza, Ann W.; Bilusic, Marijo; Rauckhorst, Myrna; Cordes, Lisa; Merino, Maria J.; Dahut, William L.; Schlom, Jeffrey; Gulley, James L.; Madan, Ravi A. (Frontiers in Endocrinology, 2020)
Medullary thyroid cancer (MTC) accounts for approximately 4% of all thyroid malignancies. MTC derives from the neural crest and secretes calcitonin (CTN) and carcinoembryonic antigen (CEA). Unlike differentiated thyroid cancer, MTC does not uptake iodine and I-131 RAI (radioactive iodine) treatment is ineffective. Patients with metastatic disease are candidates for FDA-approved agents with either vandetanib or cabozantinib, however, adverse effects limits their use. There are ongoing trials exploring the role of less toxic immunotherapies in patients with MTC. We present a 61-year-old male with the diagnosis of MTC and persistent local recurrence despite multiple surgeries. He was started on sunitinib, but ultimately its use was limited by toxicity. He then presented to the National Cancer Institute (NCI) and was enrolled on a clinical trial with heat-killed yeast-CEA vaccine (NCT01856920) and his calcitonin doubling time improved in 3 months. He then came off vaccine for elective surgery. After surgery, his calcitonin was rising and he enrolled on a phase I trial of avelumab, a programmed death-ligand 1 (PD-L1) inhibitor (NCT01772004). Thereafter, his calcitonin decreased greater than 40% on 5 consecutive evaluations. His tumor was subsequently found to express PD-L1. CEA-specific T cells were increased following vaccination, and a number of potential immune-enhancing changes were noted in the peripheral immunome over the course of sequential immunotherapy treatment. Although calcitonin declines do not always directly correlate with clinical responses, this response is noteworthy and highlights the potential for immunotherapy or sequential immunotherapy in metastatic or unresectable MTC.